Family and Staff Cooperation in Early Childhood Special Education - Nilay Kayhan; Kübra Demiröz (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: Early childhood is a critical period for supporting children's development. The role of families and the staff responsible for the services is crucial in supports to be provided in the development of children with special needs. In this study, stakeholders' cooperation processes were examined in the context of family-staff and staff-staff cooperation.Method: The participants are 12 staff and seven parents at a special education center. The data of the study, which was conducted in the phenomenological design of qualitative research methods, were obtained with the semi-structured interview technique and analyzed with content analysis.Findings: Findings were discussed under the titles cooperation experiences, family participation and needs, early childhood special education, staff, institution features, opinion and suggestions. Six main themes and 18 subthemes were reached. Discussion: The findings of the study were consistent with the findings of the studies examining the cooperation process in special education services in the literature. Physical features of the institution, its operation in accordance with legal regulations and the staff's efficiency are effective in meeting families' needs of information and social support. Families need cooperation with staff expert in different fields in the process of starting education of children with special needs after early diagnosis and evaluation. The role of families and the directors and staff of the special education institutions are critical in maintaining the cooperation. Parents' needs such as information, social and psychological support must be met in line with the family participation. Family participation should be supported through accessible digital-based cooperation programs, professional skills of staff must be developed, and the physical features of institutions must be improved.